The notosuchian record during the Cretaceous: Diversity and abundance in Argentina and its comparison with other Gondwanan landmasses - Leardi, Juan Martín (2015)
The distribution of notosuchian crocodyliforms during the Cretaceous is mostly restricted to the former Gondwanan landmasses. The objective of this contribution is to evaluate their diversity and relative abundance, both spatially and temporally. The Argentinean record is mostly represented by the one of the Neuquén basin on the Upper Cretaceous. In the Neuquén basin the most prolific unit is the Bajo de La Carpa Formation (eight valid taxa). In this context, the Argentinean record is numerically dominated by the advanced notosuchians of the genus Notosuchus, which represent more than half of the specimens found. Non ziphosuchian notosuchians are the second in abundance, although much more diverse, while sebecosuchians (and related forms) are poorly represented. This situation is quite different to the one observed in Brazil, mostly in the Bauru Basin. In this area most of the records are from the Adamantina Formation, where a very diverse crocodyliform fauna has been recovered. This assemblage is widely dominated by baurusuchid and sphagesaurid crocodyliforms, although peirosaurid taxa are quite diverse and the non sphagesaurid advanced notosuchians can be locally abundant. Both Argentinean and Brazilian records of the Lower Cretaceous are quite scarce, only represented by few basal mesoeucrocodylians. On the contrary, the African record of the Lower Cretaceous is very rich and is basically centered on the Kem Kem beds and the Gadoufaoua area. As previously reported, the taxa found in these areas are basal notosuchians, a pattern that is maintained even in the Upper Cretaceous of other areas (Maverano Formation, Madagascar).